True Infection by Capillaria hepatica in a Dog - Caparelli de Oliveira, Vanessa; Cazarini Madeira, Marina; Graneli Soares, Trayse; Rodrigues Rosado, Isabel; Martin, Ian; Ferreira Figueiredo Bittar, Joely; Gabellini Leonel Alves, Endrigo (Acta Scientiae Veterinariae, 2021)
Background: Capillaria hepatica is a nematode, zoonotic, with worldwide distribution. The main hosts are rodents, nevertheless other mammals can be affected. Although the parasite has high affinity for the liver, it rarely causes a hepatic disease in domestic animals and humans. The diagnosis is difficult and usually a biopsy is required. The treatment is difficult and is based in anti-helminthic and corticoid, but prevention is the best strategy against the disease. The aim of the present report is to describe a case of hepatic capillariosis in a dog approaching the clinical signs, diagnosis and therapeutic. Case: A 12-year-old Brazilian Terrier bitch, with a history of visit to the farm and regular hunting of rats, frogs, birds and other wild animals, was attended with hyporexia and apathy. At the physical exam the dog presented elevation of rectal temperature, intense jaundice and abdominal pain. In the biochemical exams was noticed a slight increase in globulins and a sharp increase in alkaline phosphatase (AP), total, direct and indirect bilirubin, suggesting a liver injury. In the ultrasonographic exam, hepatomegaly with dispersed hyperechoic areas were observed, suggesting hepatic steatosis. The patient was treated with ursodesoxicolic acid and S-adenosil metionin for 30 consecutive days, showing a clinic improvement. Two months after the end of the treatment the animal worsened, showing jaundice, ascites, motor incoordination, weakness, difficulty in food and water ingestion and changes in the mental state. In the complete blood count was observed a macrocytic hypochromic regenerative anemia, leukocytosis with neutrophilia and monocytosis and thrombocytopenia. In biochemical exams was detected decrease in creatinine and albumin and increase in alanine aminotransferase and AP, suggesting hepatopathy by biliary obstruction. There were performed exams for leishmania and ehrlichiosis that tested negative. In the ultrasonographic exam it was noticed that the liver had the same alterations and the presence of free fluid in the abdominal cavity. Due to the deterioration of the clinical picture a blood transfusion was necessary, however the patient worsened and presented respiratory difficulty for a bilateral pleural effusion. Then, the fluid was drained and a treatment with S-adenosil metionin, silymarin, ursodesoxicolic acid, doxycycline and prednisolone was started. After 17 days, a hepatic biopsy was performed, but the patient died at the surgery desk. Samples from the liver were collected for histopathologic exam. The diagnosis was confirmed in hepatic capillariosis and periportal chronic hepatitis, with the visualization of numerous parasites structures with bioperculated barrel shape. Discussion: Due to the nonspecific clinical alterations observed in the patient and the low prevalence of C. hepatica in domestic animals, there was a difficulty in the diagnosis which lead to a symptomatic, nonspecific and inefficient treatment that culminate with the death of the patient. The histopathologic exam of the liver is the best manner to find the correct diagnosis of C. hepatica infection, once the parasites eggs remains in the liver parenchyma wrapped by fibrosis and aren´t eliminate in the feces. The eggs elimination in the environment just occur after the death of the animal. Although there didn't exist a consensus about hepatic capillariosis treatment yet, if the diagnosis were done earlier, a specific treatment with better chances of a good result could be performed. We concluded that hepatic capillariosis should be included in differential diagnosis for patients with hepatic syndrome, mainly if the animal had a hunting habit and if it had access to surroundings with high rats’ infestation.